Self-aligned liquid crystals and enhanced electro-optical properties on solution-processed aluminum gallium tin zinc oxide surfaces - Dong Hyun Kim; Dong Wook Lee; Jin Young Oh; Jonghoon Won; Yang Liu; Dae-Shik Seo (Journal of Materials Research and Technology, 2022)
An aluminum gallium tin zinc oxide (AlGaSnZnO) film was fabricated by brush coating to create a directional micro/nano structure. Atomic force microscopy was used to observe the physical change in the film surface after brush coating, and the difference in the surface modification according to the curing temperature was analyzed through line profile and surface roughness studies. Changes in the chemical composition of the surface were analyzed through X-ray photoelectron spectroscopy. The liquid crystal (LC) alignment characteristics were analyzed through polarized optical microscopy, pretilt angle, and thermal stability tests. It was confirmed that the orientation direction of LC molecules changed from vertical to horizontal due to the difference in the surface modification at a curing temperature of 180 °C or higher, and stable LC orientation and excellent electro-optical properties were achieved. Brush-coated AlGaSnZnO film is an effective alignment film that controls the LC alignment characteristics with a simple process and can be applied in various fields.